Motor subtype changes in early Parkinson's disease. (October 2017) - Eisinger, Robert S.; Hess, Christopher W.; Martinez-Ramirez, Daniel; Almeida, Leonardo; Foote, Kelly D.; Okun, Michael S.; Gunduz, Aysegul
Abstract: Introduction: Distinct motor subtypes of Parkinson's disease (PD) have been described through both clinical observation and through data-driven approaches. However, the extent to which motor subtypes change during disease progression remains unknown. Our objective was to determine motor subtypes of PD using an unsupervised clustering methodology and evaluate subtype changes with disease duration. Methods: The Parkinson's Progression Markers Initiative database of 423 newly diagnosed PD patients was utilized to retrospectively identify unique motor subtypes through a data-driven, hierarchical correlational clustering approach. For each patient, we assigned a subtype to each motor assessment at each follow-up visit (time points) and by using published criteria. We examined changes in PD subtype with disease duration using both qualitative and quantitative methods. Results: Five distinct motor subtypes were identified based on the motor assessment items and these included: Tremor Dominant (TD), Axial Dominant, Appendicular Dominant, Rigidity Dominant, and Postural and Instability Gait Disorder Dominant. About half of the patients had consistent subtypes at all time points. Most patients met criteria for TD subtype soon after diagnosis. For patients with inconsistent subtypes, there was an overall trend to shift away from a TD phenotype with disease duration, as shown by chi-squared test, p  < 0.001, and linear regression analysis, p  < 0.05. Conclusion: These results strongly suggest that classification of motor subtypes in PD can shift with increasing disease duration. Shifting subtypes is a factor that should be accounted for in clinical practice or in clinical trials. Highlights: There exist multiple distinct motor subtypes of Parkinson's disease. The majority of Parkinson's disease patients have a tremor-dominant phenotype. Parkinson's disease subtypes vary with disease duration.